Cyanobacteria blooms before and during the restoration process of a shallow urban lake. (1st August 2017) - Rosińska, Joanna; Kozak, Anna; Dondajewska, Renata; Gołdyn, Ryszard
Abstract: Swarzędzkie Lake (near Poznań) has been heavily polluted. To improve the water quality, the restoration of lake by three methods: aeration, phosphorus inactivation using small doses of iron sulphate and magnesium chloride (FeSO4 and MgCl2 ) and biomanipulation was initiated at the end of 2011. The aim of the present study was to determine whether sustainable restoration has a significant impact on phytoplankton, especially cyanobacterial blooms in a shallow, urban, degraded lake. Therefore, phytoplankton and the physico-chemical parameters of water at the summer thermal stratification and autumn water mixing before (2011) and during restoration (2012–2014) was studied. Samples were collected at the deepest place of the lake in depth profile, every 1 m. Phytoplankton samples were preserved with Lugol's solution. The phytoplankton was counted using a Sedgewick-Rafter chamber with a volume of 0.46 ml. Measurements of water temperature were made in the field with a YSI multiparameter meter, transparency – using a Secchi disk. Concentrations of nitrogen, phosphorus and chlorophyll a were analysed in the laboratory according to Polish standards. As a result of restoration the water quality of the lake has improved. Cyanobacteria had almost disappeared during the first year of restoration, however, a short bloom was observed (dominated by Pseudanabeana limnetica ) in the second year. The main reason for this reappearance was a higher water temperature stimulating cyanobacteria growth, but an increased supply of phosphorus from the bottom sediments also contributed. A decrease in the temperature in the third year of restoration limited the growth of cyanobacteria again. Although the decrease in the phosphorus concentration as a result of restoration proved to be sufficient for average climatic conditions, it is highly likely to be more intense in the case of increased water temperature caused by global warming. Graphical abstract: Highlights: Sustainable restoration improved the lake water quality. Strong reconstruction of phytoplankton composition was observed. Short cyanobacterial water bloom appeared only in the second year of restoration. Cyanobacteria growth was stimulated by high temperature and elevated internal loading. Phosphorus decrease proved to be sufficient only for average climatic conditions.